Strategy for Developing Innovation and Environmental Awareness Through a Loofah Project-Based Learning Model: A Literature Review - Diah Ayu Ningtyas; Dea Putri Amalia; Nanang Purwanto (Bioeducation Journal, 2026)
A widespread problem currently occurring is the accumulation of plastic-based synthetic sponge waste, which poses a serious threat to the ecosystem because it produces microplastics. If this is ignored, society will feel the loss in the future. Education must be continuously carried out, especially for the younger generation, to foster a spirit of innovation and environmental awareness in a sustainable manner. Therefore, this work aims to formulate an innovation development strategy through the Project-Based Learning (PjBL) model by utilizing natural materials such as Loofah (Luffa aegyptiaca) as a creative object. This research uses a literature study method with data collection through analysis of primary and secondary literature documents related to the effectiveness of PjBL and the potential of loofah fiber. Considering the dangers of microplastic waste, this analysis includes an exploration of waste hazards, product design, and sustainability evaluation. Loofah (Luffa aegyptiaca) products can be created by adding natural colors to enhance aesthetics without damaging the ecosystem. This study shows that active involvement in the project can stimulate creative problem-solving and change the behavior of the younger generation to be more environmentally friendly. This PjBL strategy is an educational solution worthy of implementation in the world of education to create an innovative and environmentally conscious young generation. ABSTRAK Permasalahan yang marak terjadi saat ini adalah menumpuknya limbah spons sintetis berbasis plastik yang menjadi ancaman serius bagi ekosistem karena menghasilkan mikroplastik. Apabila hal ini diabaikan, masyarakat akan merasakan kerugiannya pada masa yang akan datang. Edukasi harus senantiasa dijalankan, terutama pada generasi muda, untuk menumbuhkan jiwa inovasi dan kepedulian lingkungan secara berkelanjutan. Oleh karena itu, karya ini bertujuan untuk merumuskan strategi pengembangan inovasi melalui model Project-Based Learning (PjBL) dengan memanfaatkan bahan alam Loofah (Luffa aegyptiaca) sebagai objek kreasi. Penelitian ini menggunakan metode studi pustaka dengan pengumpulan data melalui analisis dokumen literatur primer dan sekunder terkait efektivitas PjBL dan potensi serat loofah. Mengingat bahaya limbah mikroplastik, analisis ini mencakup eksplorasi bahaya limbah, rancang bangun produk, hingga evaluasi keberlanjutan. Produk Loofah (Luffa aegyptiaca) dapat dikreasikan dengan penambahan warna alami untuk meningkatkan estetika tanpa merusak ekosistem. Kajian ini menunjukkan bahwa keterlibatan aktif dalam proyek tersebut mampu merangsang creative problem solving dan mengubah perilaku generasi muda menjadi lebih ramah lingkungan. Strategi PjBL ini menjadi solusi edukatif yang layak diimplementasikan dalam dunia pendidikan untuk mewujudkan generasi muda yang inovatif dan sadar lingkungan.